Exploring Writing Test Anxiety Among EFL University Students in the Saudi Context - Mohammed Alzahrani, Eythar; Mohammed Alshaikhi, Abdullah (International Journal of English Language Education, 2023)
The purpose of this research study was threefold: (1) to investigate the levels of EFL writing anxiety, (2) identify the types of EFL writing anxiety, and (3) to find out the main causes of EFL writing anxiety. Quantitative and qualitative research methods were employed. The participants consisted of 200 students enrolled in different disciplines at King Abdulaziz University, Jeddah, Saudi Arabia. Both Second Language Writing Anxiety Inventory (SLWAI) and Causes of Writing Anxiety Inventory (CWAI) were used to collect data. The findings revealed that the majority of students (60%) experienced a high level of writing anxiety, whereas 8% of students exhibited a low level of it. In addition, cognitive anxiety was found to be the most dominant type of anxiety, while avoidance behavior was at the other end of the bar. Furthermore, causes of EFL writing anxiety among Saudi university students were in the following order: linguistic difficulties, time pressure, insufficient writing technique, insufficient writing practice, fear of teacher’s negative comments, fear of writing tests, and low self-confidence in writing.